Outcomes of Ventricular Tachycardia Ablation Using Percutaneous Left Ventricular Assist Devices. (June 2017) - Kusa, Shigeki; Miller, Marc A.; Whang, William; Enomoto, Yoshinari; Panizo, Jorge G.; Iwasawa, Jin; Choudry, Subbarao; Pinney, Sean; Gomes, Anthony; Langan, Noelle; Koruth, Jacob S.; d'Avila, Andre; et al.
Abstract : Background—: Although percutaneous left ventricular assist devices (pLVADs) facilitate mapping and ablation of hemodynamically unstable ventricular tachycardia (VT), there is limited data whether clinical outcomes are improved. We sought to retrospectively compare the outcomes of patients undergoing scar-related VT ablation with and without pLVAD support. Methods and Results—: The study population comprised 194 patients (109 pLVAD and 85 non-pLVAD). The pLVAD group more often had dilated cardiomyopathy (33% versus 13%; P =0.001), New York Heart Association heart failure class ≥III (51% versus 25%; P <0.001), lower left ventricular ejection fractions (26±10% versus 39±16%; P <0.001), and electrical storm (49% versus 34%; P =0.04). Procedure times (422±112 versus 330±92 minutes; P <0.001), postablation VT inducibility (20% versus 7%; P =0.02), and length of subsequent hospitalization (median 6 versus 4 days; P =0.001) were all higher in the pLVAD group. During median follow-up of 215 days, the primary end point (recurrent VT, heart transplantation, or death) occurred in 36% of the pLVAD versus 26% of the non-pLVAD groups ( P =0.14). After propensity matching for differences between groups, no differences were seen between groups for both acute procedural outcomes and the primary end point. Conclusions—: In this large single-center scar-related VT ablation experience, despite the worse clinical status of the patients selected for pLVAD support, clinical outcomes were better than expected and were similar to healthier patients not receiving hemodynamic support. Patients with dilated cardiomyopathy presenting with electrical storm, advanced heart failure, and severe left ventricular dysfunction most frequently received hemodynamic support during VT ablation.